BIOLOGICAL RELATIONSHIPS OF DIPLOCOCCUS INTRACELLULARIS AND GONOCOCCUS - Wollstein, Martha (The Rockefeller University Press, 1907)
The most marked differences, exclusive of pathogenic effects in man, between gonococcus and Diplococcus intracellulans are cultural ones, and consist chiefly in abundance of growth and choice of medium. Relatively larger doses of gonococci than of diplococci are required to kill young guinea-pigs, but the lesions are very similar in the two cases, and both organisms lose pathogenic power rapidly when cultivated artificially. Agglutinins, aggressins, protective power, and the amboceptors developed in the serum of immunized animals seem to be largely common to both diplococcus and gonococcus. Neither other Gram negative cocci nor Streptococcus pyogenes have any receptors in common with intracellularis and gonococcus.